Pattern Design to Optimize Transformation and Innovation Packages in Medical Education - RAZIEH ghorbandoost; hamidreza arasteh; hosein abasian; hasanreza zinababdi; aseman shafi abadi (Babol University of Medical Sciences, 2022)
Background and Objective: The purpose of this study aims to identify and explain the dimensions and components of the optimal implementation of transformation and innovation packages in medical education, which is an exceptional opportunity for educators and university officials. Methods: This qualitative study was the type of content analysis and the statistical population of research and key informants who were selected by the use of targeted sampling with snowball method. And interviews to identify dimensions have continued to ensure theoretical saturation. Data analysis was performed with Max Kuda software (10 Maxqda). Data analysis was in the content analysis quality section for validity of the Delphi technique. Findings: The findings of the study showed that the executive model of transformation and innovation packages in medical education has 9 main factors in the two sections of injuries and actions (Implementation, Structural, Politics, Environment, Management, Motivation, The proportion of abilities and jobs, cultural, leadership and 21 were sub-factors. Conclusion: The most important factor based on research data is to pay attention to the views and differences of each university and the most important factor for the optimal implementation of the transformation packages in the leadership field, and this shows us that the organization's beneficiaries are involved in formulating the strategy. Failure to achieve those goals will be a suggested approach to improving medical education.